Investigating the Composition and Metabolic Potential of Microbial Communities in Chocolate Pots Hot Springs - Fortney, Nathaniel W.; He, Shaomei; Converse, Brandon J.; Boyd, Eric S.; Roden, Eric E. (Frontiers in Microbiology, 2018)
Iron (Fe) redox-based metabolisms likely supported life on early Earth and may support life on other Fe-rich rocky planets such as Mars. Modern systems that support active Fe redox cycling such as Chocolate Pots (CP) hot springs provide insight into how life could have functioned in such environments. Previous research demonstrated that Fe- and Si-rich and slightly acidic to circumneutral-pH springs at CP host active dissimilatory Fe(III) reducing microorganisms. However, the abundance and distribution of Fe(III)-reducing communities at CP is not well understood, especially as they exist in situ. In addition, the potential for direct Fe(II) oxidation by lithotrophs in CP springs is understudied, in particular when compared to indirect oxidation promoted by oxygen producing Cyanobacteria. Here, a culture-independent approach, including 16S rRNA gene amplicon and shotgun metagenomic sequencing, was used to determine the distribution of putative Fe cycling microorganisms in vent fluids and sediment cores collected along the outflow channel of CP. Metagenome-assembled genomes (MAGs) of organisms native to sediment and planktonic microbial communities were screened for extracellular electron transfer (EET) systems putatively involved in Fe redox cycling and for CO2 fixation pathways. Abundant MAGs containing putative EET systems were identified as part of the sediment community at locations where Fe(III) reduction activity has previously been documented. MAGs encoding both putative EET systems and CO2 fixation pathways, inferred to be FeOB, were also present, but were less abundant components of the communities. These results suggest that the majority of the Fe(III) oxides that support in situ Fe(III) reduction are derived from abiotic oxidation. This study provides new insights into the interplay between Fe redox cycling and CO2 fixation in sustaining chemotrophic communities in CP with attendant implications for other neutral-pH hot springs.